1986
DOI: 10.1128/mcb.6.6.2262
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of growth phase-dependent and adenovirus 5-responsive expression of the Chinese hamster thymidine kinase gene are contained within thymidine kinase mRNA sequences.

Abstract: We have constructed a chimeric thymidine kinase (TK) minigene, pHe delta 6Ha, which combines the complete coding and 3' noncoding regions of a Chinese hamster TK cDNA with the promoter region and 5' untranslated region of the TK gene of herpes simplex virus type 1. We have transformed rat 4 cells to Tk+ with this gene and analyzed the pattern of TK gene expression in these transformants under various conditions of in vitro cell culture. We find that TK gene expression in these Tk+ transformants is growth phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…3A), we conclude that promoter and regulatory DNA sequences are present within the clone. Similar results were reported for chicken, hamster, and human tk genes isolated (4,33,42), suggesting an evolutionarily conserved, close physical linkage between tk controlling and coding regions in different species. Our observation permitted us to use the cloned mouse sequences to identify regions important for tk gene expression.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…3A), we conclude that promoter and regulatory DNA sequences are present within the clone. Similar results were reported for chicken, hamster, and human tk genes isolated (4,33,42), suggesting an evolutionarily conserved, close physical linkage between tk controlling and coding regions in different species. Our observation permitted us to use the cloned mouse sequences to identify regions important for tk gene expression.…”
Section: Methodssupporting
confidence: 76%
“…These results are in agreement with a recent report by Hofbauer et al (23), showing that expression of the mouse tk cDNA is dramatically reduced in cells arrested in the G1 phase of the cell cycle by sodium butyrate. Other groups have also found that hamster and human tk cDNAs contain sequences mediating increased TK enzyme activity in association with the entry of cells into the S phase of the cell cycle (33,55 Fig. 4H]).…”
Section: Methodsmentioning
confidence: 99%
“…Like ODC, serum-induced changes in chicken [39] and mouse [40] TK mRNAs are smaller than changes in activity. Regulation of cytosolic TK in mouse L-MTK- [40] and rat-4 [41] cells has been shown, by methods similar to those reported here, to have components localized within the protein coding region. The mouse TK gene contains additional determinants outside the coding region that regulates an additional 4 to 5-fold change in mRNA levels.…”
Section: Odc Lability and Its Effect On Regulationmentioning
confidence: 56%
“…The situation has been further complicated by the fact that hybrid TK genes utilizing heterologous promoters are cell cycle regulated in several systems (13,16); this has led investigators to conclude that transcriptional control is not occurring. In fact, the presence of dual levels of control is now established for many of the S phase-regulated genes that have been examined.…”
Section: Resultsmentioning
confidence: 99%